Penerapan Struktur Tiga Babak dalam Penulisan Naskah Video Feature “Melodi Bambu: Menghidupkan Kembali Simfoni Tradisonal” - Alfan Zibran Aulia Il Ghani; Encang Encang; Ari Agung Prastowo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This final project report aims to explain the application of a three-act structure in writing a feature video script entitled "Bamboo Melody: Reviving a Traditional Symphony." The three-act structure is used as a narrative approach that functions to raise the issue of the fading of the angklung's sound philosophy among Generation Z. Each act plays an important role in building a structured and easily understood storyline for the audience. The first act focuses on the introduction of the angklung's philosophical meaning. In this act, the audience is invited to understand more deeply about the cultural values contained in the angklung, especially through the perspective of angklung craftsmen who have a direct relationship with the creation of this traditional musical instrument. The explanations from the craftsmen provide an overview of how the angklung is not only a musical instrument, but also a symbol of a profound philosophy of life. The second act highlights the crisis of cultural regeneration, which is a major challenge in preserving traditions. In this act, the perspective of cultural experts is introduced to provide an analysis of how the younger generation, especially Generation Z, is increasingly alienated from traditional cultural values, including the angklung. Cultural experts explain various factors that cause the angklung and other cultural values to be less familiar to the younger generation, who are more accustomed to global popular culture. The third act demonstrates concrete efforts to preserve angklung culture through testimonies from young angklung players and performances at Saung Angklung Udjo. Through this performance, the audience sees how the angklung remains relevant and can be revived by involving a younger generation that is adaptable to developments in media and technology. The story's conclusion illustrates that cultural regeneration can be achieved through a creative approach and the active involvement of the younger generation, so that the angklung's sound philosophy becomes more than just a discourse but can also contribute to social harmony relevant to the current context.